Cannon Ball Tree, Trinidad, B.W.I. - 19 - (:unkn) unknown (My University, 2010)
A photo of a Cannon ball tree heavily laden with fruits.
Colour: Black and white; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Couroupita guianensis; Trees--Trinidad and Tobago; Cannon ball tree--Trinidad and Tobago